Identification and Isolation of Japanese Encephalitis Virus Genotype IV from Culex vishnui Collected in Bali, Indonesia in 2019 - Faizah, Astri Nur; Kobayashi, Daisuke; Maekawa, Yoshihide; Amoa-Bosompem, Michael; Fauziyah, Shifa; Mulyatno, Kris Cahyo; Subekti, Sri; Rohmah, Etik Ainun; Lusida, Maria Inge; Mori, Yasuko; Miura, Kozue; Hirayama, Kazuhiro; et al. (The American journal of tropical medicine and hygiene, 2021)
Japanese encephalitis virus (JEV) is transmitted between swine, migratory birds, and Culex mosquitoes, and has circulated indigenously in Asia for almost a century. Despite being the country with the highest JEV diversity, surveillance targeting of Indonesia’s vectors is scarce. This study collected mosquitoes from several locations in Tabanan Regency, Bali Island, Indonesia. We captured and classified 3,032 adult Culex mosquitoes into seven species, with Culex vishnui subgroup mosquitoes making up approximately 90% of the total. Japanese encephalitis virus was identified by next-generation sequencing (NGS) analysis of a Cx. vishnui mosquito pool. Genetic and phylogenetic analysis revealed the JEV as genotype (G) IV. The nucleotide identity was 99% with other JEV GIV isolates obtained from swine sera in 2017 on Bali Island and from a human patient in Australia with a travel history to Bali in 2019. This finding indicated that JEV GIV persists in restricted areas and is circulating between swine-mosquito vectors.